Answer:
Step-by-step explanation:
so we can use [tex]t^{2}[/tex] + 25 as one expression and the find the distance between the points and set the expression equal to that number. That's our strategy.
dist = the square root of [tex]x^{2}[/tex] + [tex]y^{2}[/tex]
where x and y are the change in x2 to x1 and y2 to y1
P1 = ( -3, -5)
P2 = (2, 7 )
dist = square root of ( [2 -(-3) ]^2 + [7-(-5)]2)
dist = sq rt ( 5^2 + 12^2 )
dist = sq rt ( 25 + 144)
dist = sq rt (169)
dist = 13
now set our eq. equal to that number
[tex]t^{2}[/tex] + 25 = 13
[tex]t^{2}[/tex] = -12
this is looking kinda bad, do you know complex numbers?
t = 0 + j 3.46410
hmmm I'm wondering if you've left out .. or forgotten some thing in the question? :/